The Identification of Electrical Properties of Acupuncture Points for Asthma Diagnosis - Prijo, Tri Anggono; Risti, Norienna Valendiani; Kawitana, Welina Ratnayanti (Indonesian Applied Physics Letters, 2021)
The aim of this research is to identify the electrical potential profile on the acupoint betwen healthy people and the patient of asthma. The raw data has taken by recording the electrical potential profile on the acupoints: Feishu, Pishu, and Shenshu from 10 healthy women and the 10 women with asthma attain the age of 20-30 years old based on the second data observation at the Local Government Clinic Kalijudan, Surabaya. Potential profile of the organs were the electrical signals form. It was achieved by the result of electrical potential which was based time recording. Recording time was done for 180 second. The results couldn't be differentiated significantly, so it needs the other signals processing with FFT analyze method with cutting as the data frames. It was done every 5 second. Based on the result of analyzing the amplitude of each frequency group, the significant differences are on the acupoint Shenshu : 0-5 Hz with p= 0.001, on the acupoint Phishu 148-152 Hz with p= 0.010, on the acupoint Feishu for frequency 198-203 Hz with p= 0.004 and on the acuponit Phishu p=0.011, for frequency 348-352 Hz on the acupoint Feishu and Shenshu have both value is p= 0,004 and 398-402 Hz with p=0,009 on the acupoint Phishu. According to the preference, it was found that the electrical potential profile on the acupoints of the healthy people has lower amplitude than the people with asthma. Then, the analyze of electrical potential profile on the acupoints can be used for asthma diagnose.